Clinico-Epidemiological Study of Bovine Forestomach Disorders - Biradar, Sanjay Kumar; Bhatt, Raghuvir H; Padaliya, Nilesh R; Dodi, Vaibhav D; Vadalia, Jignesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to determine the clinico-epidemiological status of bovine forestomach disorders among 11,047 bovines which were presented during the period of three years (January 2021- December 2023) at Veterinary Clinical Complex of the College in Junagadh (Gujarat). Among these, 2279 (20.63%) were suffering from different surgical diseases, and out of them, 239 (10.48%) were diagnosed with different forestomach disorders. Age wise highest incidence was recorded in the age group of 6 to 10 years (60.66%), followed by up to 5 years (26.77%), 11 to 15 years (10.87%) and 16 to 20 years (1.67%). Females (89.53%) were more affected as compared to male animals (10.46%), and breed wise distribution showed a higher number of cases in Jaffarabadi buffaloes (43.09%), followed by non-descript buffaloes (21.75%), Gir cattle (20.50%), non-descript cattle (8.78%), Kankrej cattle (5.43%) and Holstein Friesian cattle (0.41%). The different type of forestomach disorders recorded were traumatic reticuloperitonitis (27.61%), diaphragmatic hernia (20.92%), traumatic reticulopericarditis (20.92%), rumen impaction (16.31%), traumatic reticulitis (5.43%), omasal impaction (4.18%), reticular abscess (2.92%), rumen fistula (0.83%) and rumen hernia (0.83%). The findings signify the need of early diagnosis and management of these cases to safeguard the life of animal and economy of the farmer.